How to Use Cobit Applications in Educational Institutes (International Journal of Management and Sustainability, 2014)
Decision makers are looking at all expenditures to see where to cut costs and install greater IT systems management efficiencies. For implementation of an IT governance program successfully, it is important to understand management needs. IT service management is becoming more important in any kind of business sector including in higher education sector or university education. In the university education system, it can be used to enhance competitiveness and performance of related stakeholders. IT infrastructure is growing increasingly complex as different technological advancements, such as IT governance (by some special methodologies like Control Objectives for Information and Related Technology (CoBIT) & Information Technology Infrastructure Library (ITIL) etc.) and cloud computing, continue to enhance higher education networks. These systems management solutions can be very helpful to facilitate greater collaboration in learning and educational management. In this study we investigated the problems of the Atılım University students ‘n Turkey about the course control system (Focusing on Time-Table scheduling system). In the survey we asked questions about registration process, time table managements, exam time clashes, course loads, student satisfaction about the time table and exam allocation system. The results are gathered, analyzed and documented and the results are discussed. Depending on the results we proposed a CoBIT methodology to improve the student satisfaction.